2021
DOI: 10.1016/j.xpro.2021.100788
|View full text |Cite
|
Sign up to set email alerts
|

Integrated protocol for exitron and exitron-derived neoantigen identification using human RNA-seq data with ScanExitron and ScanNeo

Abstract: Summary Exitron splicing (EIS) events in cancers can disrupt functional protein domains to cause cancer driver effects. EIS has been recognized as a new source of tumor neoantigens. Here, we describe an integrated protocol for EIS and EIS-derived neoantigen identification using RNA-seq data. The protocol constitutes a step-by-step guide from data collection to neoantigen prediction. For complete details on the use and execution of this protocol, please refer to Wang et al. (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…117,125,126 The production of neoantigens from skipped exons, also known as "neojunctions", occurs more frequently and is more likely to be shared among patients than those generated from SNV mutations. 29,117,127,128 A recent study has identified exitron splicing, a non-canonical splicing mechanism, as a new source of tumor neoantigens. Exitrons are exon-embedded cryptic introns distinguished from conventional introns in that they have both splicing (intron) and protein-coding (exon) potential while lacking stop codons or premature termination codons.…”
Section: Transcriptomic Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…117,125,126 The production of neoantigens from skipped exons, also known as "neojunctions", occurs more frequently and is more likely to be shared among patients than those generated from SNV mutations. 29,117,127,128 A recent study has identified exitron splicing, a non-canonical splicing mechanism, as a new source of tumor neoantigens. Exitrons are exon-embedded cryptic introns distinguished from conventional introns in that they have both splicing (intron) and protein-coding (exon) potential while lacking stop codons or premature termination codons.…”
Section: Transcriptomic Variantsmentioning
confidence: 99%
“…Accordingly, exitrons splicing creates more validated neoantigens with higher immunogenicity in malignancies with low TMB. 128,129 Trans-acting alterations in splicing factors. Trans-acting alterations, in which a somatic mutation in a splicing factor results in an altered splicing variant, induce the production of neoantigens throughout the genome.…”
Section: Transcriptomic Variantsmentioning
confidence: 99%
“…3B ). Wang and Yang (2021) , using a bioinformatic tool named ScanExitron, identified exitron splicing in 33 cancer types across 9599 tumour transcriptome data. They observed that exitron splicing affected 63 % of the coding genes of humans, and 95 % of these exitronic events were tumour specific.…”
Section: Function Of Exitronsmentioning
confidence: 99%
“…They identified exitron splicing-derived neo-epitopes, which can bind to MHC Class I or II and potentially be targeted for immunotherapy. An integrated protocol for the identification of exitron and exitron-derived neo-antigen using RNA-seq data using bioinformatic tools like ScanExitron and Scan Neo was developed by Wang and Yang (2021) . Splicing of exitrons was observed in genes like TAF15 , FUS and EWSR1 , which may be involved in promoting cancer progression ( Zhang et al 2022 ).…”
Section: Function Of Exitronsmentioning
confidence: 99%
“…INDELs were called by TransIndel [40] followed by neoepitopes analysis by ScanNeo [41] and calls present in healthy controls were removed. Exitrons were called by ScanExitron [42] and ScanNeo further predicted neoantigens (Table S1). visual overview of workflow.…”
Section: Neoepitopes Derived From Indels and Exitronsmentioning
confidence: 99%